An existence result for quasilinear parabolic systems with lower order terms - Balaadich, Farah; Azroul, Elhoussine (Mathematical Modelling and Analysis, 2021)
In this paper we prove the existence of weak solutions for a class of quasilinear parabolic systems, which correspond to diffusion problems, in the formwhere Ω is a bounded open domain of be given and The function v belongs to is in a moving and dissolving substance, the dissolution is described by f and the motion by g. We prove the existence result by using Galerkin’s approximation and the theory of Young measures.